Assessing the stability of fiscal attitudes: Evidence from a survey experiment. (4th May 2021) - Tuxhorn, Kim‐Lee; D'Attoma, John; Steinmo, Sven
Abstract: The literature on attitudes toward government budgets has been dominated by two distinct approaches, jointly studying both sides of the ledger (holistic approaches) and studying attitudes over spending and revenue separately (singular approaches). Despite both approaches being widely adopted, scholars have given limited attention to testing empirically how methodological differences in the approaches may affect measures of fiscal attitudes and the inferences we draw from those measures. In this paper, we ask, "Do the different approaches to studying the budget alter mass attitudes toward spending and taxes, and if so, how?" Using data from an Amazon MTurk survey experiment, we find that spending choices differ significantly (attitude instability) across the two approaches. On the revenue side, our results show that choices over taxation tend to remain consistent and stable, regardless of whether the choices include only taxes or the combination of taxes and spending. Abstract : 정부 예산에 대한 개인의 태도/의견을 연구하는 기존 연구는 통상 두 가지 접근 방법을 취해왔다. 정부의 지출과 수익을 함께 연구하는 "전체론적 접근법"과 이 둘을 별도로 구분, 연구하는 "단일 접근법"이 그것이다. 이 두 가지 접근법이 널리 채택되고 있음에도 불구하고, 접근법의 차이가 재정에 대한 태도를 측정하고 이해하는 데 어떠한 영향을 미치는지에 대해서는 전반적으로 학술연구가 제대로 이루어져 있지 않다. 이에 본 연구의 목적은 예산 연구의 접근법에 따라 정부의 지출과 세금에 대한 개인의 의견이 현저하게 달라지는지, 만약 달라지면 어떻게 달라지는지를 규명하는 데 있다. 아마존 머케니컬터크 (Amazon MTurk)를 통해 진행된 설문 실험을 통해, 본 연구는 (1) 연구 접근법의 차이에 따라 정부 지출에 대한 참여자들의 의견은 유의미하게 달라지면서도, (2) 수익과 관련하여서는, 연구 접근법에 상관없이 세금에 대한 참여자들의 의견은 일관됨을 발견하였다. 이와 같은 세금에 대한 선호의 일관성은 개인들이 정부 수입에 대해서 명확한 의견이 있음을 보여주는 기존의 경험적 연구와 일치한다.